Inteligent CAD-CAP Interface Based on Feature Recognition nd Genetic Algorithm - Miran Brezocnik; Igor Drstvensek (Communications - Scientific letters of the University of Zilina, 2000)
The integration of production depends mainly on an automation level of the existing production cells that will be integrated into a common information system. In terms of CIM it means integration of CAD and CAM tasks. The integration also demands taking the CAP tasks into an account, because of their intermediate position. The paper describes an intelligent interface for integration of CAD and CAP tasks. It consists of two parts, recogniser and seeker. The recogniser scans the CAD model and recognises its features. The seeker uses the results of the recogniser as an input and searches the appropriate work operation from the technological database. The seeker uses genetic algorithm (GA) optimisation principles for finding the optimal machining procedure of the CAD part.